АБУ РАЙХАН БЕРУНИЙДИҢ ФИЛОСОФИЯЛЫҚ КӨЗҚАРАСЛАРЫНДА БИЛИЎДИҢ ГЕЙПАРА МӘСЕЛЕЛЕРИ ҲАҚҚЫНДА - Есназарова, З.; Тилеўмуратова, З. (FAN va JAMIYAT, 2020)
The study of issues of importance, laws and peculiarities of formation and development of cognition has taken an important place in the history of philosophy. The article deals with the philosophical views of Abu Rayhan Beruni on the main points of cognition theory. The great thinker and scientist paid much attention in his works to the issues of cognition methods and ways and scientific methods.